Pengelolaan Bank Sampah dan Pembuatan Pupuk Organik Cair di Dukuh Kalangan Desa Genengsari - Pitasari, Desandromedha; Sutrisno, Wahyudhi; Maskuri, Ali; Prabaswari, Atyanti Dyah (Universitas Islam Indonesia, 2025)
Waste management in Dukuh Kalangan, Desa Genengsari, is the primary focus of this community service, particularly aimed at enhancing the efficiency of waste management and utilizing organic waste for the production of Liquid Organic Fertilizer (LOF). The objective of this community service program is to reduce agricultural input costs and increase community awareness and participation in sustainable waste management practices. The methodology employed includes socialization, distribution and education on the use of trash bags, the collection and processing of organic waste, as well as monitoring and evaluating the quality of LOF. The data collected shows a significant improvement in community understanding and skills in sorting and processing waste. As a result, the community has become more self-reliant in meeting their fertilizer needs and contributes to sustainable waste management practices.